A case of asymptomatic ST segment changes in cyclist with two myocardial bridges - Stefano Giraudi; Barbara Severgnini; Paolo Valli; Anna Teresa Pandiscia; Lucrezia Marchetti; Silvana Scarpini (Journal of Health and Social Sciences)
A 65-year-old male regularly involved in competitive cycling came to our sports medicine laboratory for the annual mandatory pre-participation screening. Cycling screening protocol includes a cardiological examination, basal ECG and cardiac stress test. The clinical examination was unremarkable, and the patient’s blood pressure was 120/75 mmHg. The rest-ECG was normal. The ardiac exercise stress test showed a 2 mm ST-segment inversion in the anterior leads (V3-V4-V5-V6) at peak exercise. No presence of arrhythmias or symptoms were reported. Due to an ST segment depression recorded during the cardiac exercise stress test, we performed a coronary computed tomography angiography (CCTA) that showed two myocardial bridges of the left coronary artery. However, we observed no atherosclerotic plaque of the coronary lumen. A dobutamine stress echocardiogram and a bicycle stress echocardiogram were normal. We concluded for ventricular repolarisation abnormalities during maximal exercise testing due to the electrocardiographic findings in an asymptomatic athlete without any coronary artery disease. In literature, myocardial bridging is regarded as a common anatomic variant rather than a congenital anomaly. Nevertheless, some reports show that myocardial ischemia and myocardial infarction or sudden death could be caused by myocardial bridging. In addition, intramyocardial bridging is a recognised cause of sudden death in athletes. Therefore, according to the Italian cardiological guidelines for competitive sports (COCIS 2009), we recommended the patient avoid physical overload and sport practice.